2015
DOI: 10.3892/ol.2015.3373
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of short TRPM8 variant α promotes cell migration and invasion, and decreases starvation-induced apoptosis in prostate cancer LNCaP cells

Abstract: Abstract. The aim of the present study was to investigate the function of a transient receptor potential melastatin 8 (TRPM8) splice variant, short TRMP8α (sM8α), in the androgen-dependent prostate cancer LNCaP cell line, and to evaluate the potential involvement of the mitogen-activated protein kinase (MAPK) signaling pathway. The coding DNA for sM8α was cloned and transfected into LNCaP cells to generate cells that overexpress this isoform of TRPM8. Cellular proliferation was determined by performing an MTT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 19 publications
1
35
1
Order By: Relevance
“…In addition to full-length transcripts, short sM8α and sM8β were generated from the TRPM8 gene through alternative splicing regulation [65]. Spatial expressions of TRPM8 isoforms were noted in lung tissues and prostate cancer [67]. These short transcripts encode the N-terminus region of the TRPM8 protein, and were demonstrated to manipulate the activity and sensitivity of authentic TRPM8 [67].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to full-length transcripts, short sM8α and sM8β were generated from the TRPM8 gene through alternative splicing regulation [65]. Spatial expressions of TRPM8 isoforms were noted in lung tissues and prostate cancer [67]. These short transcripts encode the N-terminus region of the TRPM8 protein, and were demonstrated to manipulate the activity and sensitivity of authentic TRPM8 [67].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
“…Spatial expressions of TRPM8 isoforms were noted in lung tissues and prostate cancer [67]. These short transcripts encode the N-terminus region of the TRPM8 protein, and were demonstrated to manipulate the activity and sensitivity of authentic TRPM8 [67]. Overexpression of sTRPM8α, but not sTRPM8β, substantially abolished starvation-induced apoptosis of several prostate cancer cells [66].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Activities of TRPM8 were required for the chemotaxis and migration of glioblastoma cells (T98G and U-87MG) as shown by siRNA-mediated downregulation of TRPM8, pharmacological inhibition by the TRP channel blocker BCTC or TRPM8 activation by icilin (Klumpp et al, 2017). The authors reported that TRPM8 promoted migration of these glioblastoma cells possibly through activation of Ca 2+ -regulated K + channel, that is, big conductance Moreover, independent groups of researchers demonstrated that TRPM8 short isoforms localized in the cytoplasm (in contrast to the full-length TRPM8 localized on the plasma membrane) were required for the survival, migration, and invasion of prostate cancer cells (LNCaP; Bidaux et al, 2016;Peng et al, 2015). Multiple non-channel cytoplasmic TRPM8 isoforms, consisting of sM8α, sM8β, sM8γ, sM8δ, sM8ε, sM8ζ, and sM8η (both sM8ζ and sM8η do not encode protein), collectively termed as sM8, were found to be expressed in prostate cancer cell lines (PC3, LNCaP, and LNCaP C4-2b; Bidaux et al, 2016).…”
Section: Trpm8: Oncogenic Cytoplasmic Localization and Short Isoformsmentioning
confidence: 99%
“…, ), whereas the short TRPM8 isoform could have a pro‐metastatic potential (Peng et al . ; Bidaux et al . ).…”
Section: Introductionmentioning
confidence: 99%